Situating Sexual Violence in Rwanda (1990–2001): Sexual Agency, Sexual Consent, and the Political Economy of War - Burnet, Jennie E. (African studies review, 2012)
This article situates the sexual violence associated with the Rwandan civil war and 1994 genocide within a local cultural history and political economy in which institutionalized gender violence shaped the choices of Rwandan women and girls. Based on ethnographic research, it argues that Western notions of sexual consent are not applicable to a culture in which colonialism, government policy, war, and scarcity of resources have limited women’s access to land ownership, economic security, and other means of survival. It examines emic cultural models of sexual consent and female sexual agency and proposes that sexual slavery, forced marriage, prostitution, transactional sex, nonmarital sex, informal marriage or cohabitation, and customary (bridewealth) marriages exist on a continuum on which female sexual agency becomes more and more constrained by material circumstance. Even when women’s choices are limited, sometimes impossibly limited, they still exercise their agency to survive. Conflating all forms of sex in conflict zones under the rubric of harm undermines women’s and children’s rights because it reinforces gendered hierarchies and diverts attention from the structural conditions of poverty in postconflict societies